THE DIALECTICS OF THE ABSTRACT AND SPECIFIC IN L.S.VYGOTSKY’S WORKS - Papucha, Mykola (PSYCHOLOGICAL JOURNAL, 2020)
The article analyzes the complex interaction of the abstract and specific in L.S.Vygotsky’s works. The specific is analyzed as a unity in diversity, as a complex, contradictory, heterogeneous and nonlinear-logic unity. We have proven that L.S.Vygotsky, searching for such content-rich specific that can be a «cell» in psychology, implemented actually the idea of systematicity in psychology. The advantages of «unit analysis» are explicated in view of the fact that a “unit” (unlike an “element”) includes the most simple as well as learnable form of everything that in its “unfolded” state (mentally, on the basis of accumulated scientific facts) allows getting truly specific knowledge. The general way of cognition is pointed out: a philosophical and methodological idea about an object (abstract) - contemplation - analysis – finding of specific-universal - practice - new methodology etc. – the spiral of cognition. A task (supertask) of L.S.Vygotsky’s cultural and historical theory was to build (to unfold) the specific human psychology as a modus (“unit”) of substance. Methodological principles of monism, indeterminism and systematicity are described as fundamental ones in psychology. L.S.Vygotsky’s works highlight Spinoza’s understanding of eternal development, so the concept of development becomes even not a principle but the fabric of a study subject in Vygotsky’s theory. The inner unity of psychology is explained as the most complex relationship of biological and psychical attributes and connections within the psychological domain. Inter-functional psychological systems include not only components of higher mental functions but also natural, biological and cultural ones, namely everything that is covered by “a human being’s psychological life” as a concept. There are many systems, but they are interconnected, forms semantic dynamic systems after emergence of conceptual thinking. We should mention that relations embrace all human personality, they are constantly changes as for their essence and they are the main key to understanding of a human being. “Affect – intellect” antinomy is understood in the sense that all the phenomena from both conscious and unconscious domains, being actualized into an event.